PERAN MEDIA DALAM MENDUKUNG PENGEMBANGAN MOTIVASI BELAJAR SISWA DI ERA MODERN - Desi Trikesumawati; Moh Wajdy Ishamy; Moh Rafi Rizqullah (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study aims to examine the role of modern-era learning media in enhancing student learning motivation. Technology-based learning media, such as educational applications, interactive videos, and online platforms, have proven effective in creating engaging and relevant learning experiences for students. Through a literature review, this research found that the use of learning media not only increases student engagement but also strengthens their intrinsic motivation. Moreover, teachers play a crucial role in optimizing the use of media to create a conducive learning environment, involve students in the evaluation process, and provide constructive feedback. The combination of these strategies has been shown to significantly enhance students' learning motivation. Thus, this study emphasizes the importance of integrating technology into learning to support better educational outcomes in the modern era.